Finite element method (FEM) simulation of compression tests with imperfect dimension - Hoi, Yu Xuen (Nanyang Technological University, 2023)
This report details the development of static compression test simulations with imperfect dimensions using Finite Element Method (FEM). The purpose of this study is to simulate the responses of the alloy Aluminium 6061 T6 to imperfect surface parallelism, under compressive loading. The compression test model generated will strictly comply to the conditions specified by the American Society for Testing Materials (ASTM) E9 International Standards, in order to achieve results approximating actual tests. The FEM software used is ANSYS Workbench 2022 R2, where geometric models with varying degrees of imperfections will be imported and processed for computational analysis. Detailed procedures along with explanations are provided in this report to ensure repeatability in future studies. Results obtained are evaluated to determine the effects of the mentioned imperfection, followed by establishing probable causes. Lastly, the report seeks the possibility of relieving the parallelism tolerance set by international standards in order to facilitate specimen preparation.